Mechanical force regulates root resorption in rats through RANKL and OPG - Jianli Zhou; Lijia Guo; Yanji Yang; Yi Liu; Chen Zhang (BMC, 2022)
Abstract Background External root resorption is one of common complications of orthodontic treatment, while internal root resorption is rarely observed, and the difference between pulp and periodontal tissues during orthodontic treatment is still unknown. The purpose of this study was to evaluate the effects of orthodontic forces on histological and cellular changes of the dental pulp and periodontal tissues. Methods Orthodontic tooth movement model was established in Forty-eight adult male Wistar rats. The distance of orthodontic tooth movement was quantitatively analyzed. The histological changes of pulp and periodontal tissues were performed by hematoxylin-eosin staining, tartrate-resistant acid phosphate staining was used to analyze the changes of osteoclast number, immunohistochemistry analysis and reverse transcription polymerase chain reaction were used to examine the receptor of nuclear factor-κB ligand (RANKL) and osteoprotegerin (OPG) expression. The width of tertiary dentine was quantitatively analyzed. Tartrate-resistant acid phosphate staining and the erosion area of osteo assay surface plate was used to evaluate osteoclast activity. Results The orthodontic tooth movement distance increased in a force dependent manner, and reached the peak value when orthodontic force is 60 g. Heavy orthodontic force increased the RANKL expression of periodontal ligament srem cells (PDLSCs) which further activated osteoclasts and resulted in external root resorption, while the RANKL expression of dental pulp stem cells (DPSCs) was relatively low to activate osteoclasts and result in internal root resorption, and the dental pulp tend to form tertiary dentine under orthodontic force stimulation. Conclusions Heavy orthodontic forces activated osteoclasts and triggered external root resorption by upregulating RANKL expression in rat periodontal tissues, while there was no significant change of RANKL expression in dental pulp tissue under heavy orthodontic forces, which prevented osteoclast activation and internal root resorption.